A Prospective Study on the Prescription Pattern of Anti-Epileptic Drugs in Pediatric Patients - Raj, Kishore Harshavardhan; Yadav, Shekhar; Murthy, Sudha; George, Blessy; Ramaiah, Balakeshwa (Indian Journal of Pharmacy Practice)
Background: Seizures are sudden, temporary episodes of brain activity that cause changes in behavior, sensation or consciousness and lead to uncontrollable movements. With the expanse of study on seizures, numerous therapeutic measures exist in treating this disease, it is imperative to formulate and develop a comprehensive treatment plan when encountering a patient with either seizure or epilepsy. Materials and Methods: This prospective, observational study was performed in a tertiary care hospital, Bengaluru in the pediatric department. The data obtained from the paediatric patients ranged from demographic data, age distribution, primary seizure or epilepsy diagnosis, number of seizure and or epileptic episodes experienced by the patients and data was documented in a standard data collection form. Results: The analysis population comprised 47 pediatric patients. The finding revealed a preponderance of patients <1 year were more likely affected with 36.17%. The diagnostic results state that a majority of the seizure patients presented with epilepsy (n=15) followed by a tie between status epilepticus (n=6) and febrile seizure (n=6). A large portion of the study population (n=19, 40.42%) were administered Levetiracetam as the mainstay for seizures. Conclusion: The conclusion of this study yields the fact that the most prescribed Antiepileptic Drug (AED) was Levetiracetam as it has proven its efficacy. The gender distribution saw a marked difference between the male and female patients, whereby, there were 32 and 15 male and female patients respectively. The distribution of seizure and epilepsy cases in the study population was 17 and 30 cases respectively.
Keywords: Anti-epileptic drugs; Epilepsy; Levetiracetam; Pediatrics; Seizure